Whortleberry protects kidney against the cisplatin-induced nephrotoxicity: an experimental study. (15th October 2018) - Eren, Huseyin; Aydin, Hasan Riza; Tumkaya, Levent; Kazaz, Ilke Onur; Kalkan, Yildiray; Kazaz, Seher Nazli; Mercantepe, Tolga; Horsanali, Mustafa Ozan; Yilmaz, Adnan
Abstract: Purpose: This study investigated the antioxidant effects of whortleberry against cisplatin-induced nephrotoxicity in rats. Material and methods: This study included 48 female Sprague–Dawley rats weighing 263.68 ± 8.29 g. The rats were divided into the following six groups, with eight rats in each group: control, ethanol control, whortleberry control, cisplatin control, 16 mg/kg cisplatin +100 mg/kg whortleberry, and 16 mg/kg cisplatin +200 mg/kg whortleberry groups. Biochemical analysis was performed by measuring total oxidant status and total antioxidant status, histopathological analysis was performed by calculating proximal and distal tubule areas (μm 2 ), and immunohistochemical analysis was performed by determining anti-Caspase-3 immunostaining. Differences among the groups were examined using one-way analysis of variance, and p  < .05 was considered statistically significant. Results: Cisplatin treatment decreased the total antioxidant status and increased the total oxidant status and Caspase-3 level. Moreover, it resulted in the dilatation, vacuolization and loss of tubular epithelial cells; and glomerular degeneration and edema in the kidney tissues ( p  < .05). Treatment with 100 and 200 mg whortleberries increased the total antioxidant status; decreased the total oxidant status and Caspase-3 level and ameliorated distal and proximal tubule degeneration, glomerular degeneration and edema in the kidney tissues ( p  < .05). Conclusions: Our results indicate that the antioxidant effects of the whortleberry decrease cisplatin-associated nephrotoxicity.